Convenient Clothing Pattern and Colour Recognition for People with Vision Impairment - kumar.R, Vijay; V, Vishwas.; M, Bharath.; kumar.R, Yathish; S, Veena. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The objective of this paper is to design and implement a prototype which is capable of recognizing clothing patterns in four categories (plaid,plain,irregular,striped) and identifies 12 colors. Choosing clothes with complex patterns and colors is a challenging task for visually impaired people. We have developed a camera-based prototype system that has an integrated camera, a microphone, a computer, and a Bluetooth earpiece for audio description of clothing patterns and colors. The clothing patterns and colors are described to blind users orally. This system can be controlled by speech input through microphone. To recognize clothing patterns, we propose a novel Radon Signature descriptor and a schema to extract statistical properties from wavelet sub-bands to capture global features of clothing patterns. To evaluate the effectiveness of the proposed approach, we used the CCNY Clothing Pattern dataset. Our approach achieves 90% recognition accuracy which significantly outperforms the state-of-the-art texture analysis methods on clothing pattern recognition.